Angiotensin-(1-7) Promotes Resolution of Neutrophilic Inflammation in a Model of Antigen-Induced Arthritis in Mice - Barroso, Lívia C.; Magalhaes, Giselle S.; Galvão, Izabela; Reis, Alessandra C.; Souza, Daniella G.; Sousa, Lirlândia P.; Santos, Robson A. S.; Campagnole-Santos, Maria Jose; Pinho, Vanessa; Teixeira, Mauro Martins (Frontiers in Immunology, 2017)
Defective resolution of inflammation is crucial for the initiation and development of chronic inflammatory diseases, such as arthritis. Therefore, it has been suggested that therapeutic strategies based on molecules that facilitate inflammation resolution present great potential for the treatment of chronic inflammatory diseases. In this study, we investigated the role of angiotensin-(1-7) [Ang-(1-7)] in driving resolution of neutrophilic inflammation in a model of arthritis. For this purpose, Male C57BL/6 mice were subjected to AIA and treated with [Ang-(1-7)] at the peak of the inflammatory process. Analysis of the number of inflammatory cells, apoptosis and immunofluorescence for NF-κB were performed in the exudate collected from the knee cavity. Neutrophil accumulation in periarticular tissue was measured by assaying myeloperoxidase (MPO) activity. Apoptosis of human neutrophil after treatment with Ang-(1-7) was evaluated morphologically and by flow cytometry, and NF-κB phosphorylation by immunofluorescence. Efferocytosis was evaluated in vivo. Therapeutic treatment with Ang-(1-7) at the peak of inflammation promoted resolution, an effect associated with caspase-dependent neutrophils apoptosis and NF-κB inhibition. Importantly, [Ang-(1-7)] was also able to induce apoptosis of human neutrophils, an effect associated with NF-B inhibition. The pro-resolving effects of angiotensin-(1-7) were inhibited by the Mas receptor antagonist A779. Finally, we show that [Ang-(1-7)] increases the efferocytic ability of murine macrophages. Our results clearly demonstrate that angiotensin(1-7) resolves neutrophilic inflammation in vivo acting in two key step of resolution- apoptosis of neutrophils and their removal by efferocytosis. [Ang-(1-7)] is a novel mediator of resolution of inflammation.